2008
DOI: 10.1159/000118792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis E Virus IgG Antibody in Japanese Patients with Hemophilia

Abstract: Objective: We investigated the prevalence of antibody against hepatitis E virus (HEV) in Japanese patients with hemophilia. Methods: IgG antibody against HEV was measured in serum of 80 Japanese patients with hemophilia by enzyme-linked immunosorbent assay. The prevalence of HEV antibody was compared with the reported prevalence of HEV antibody in Japanese patients undergoing hemodialysis and in Japanese healthy blood donors. Characteristics of patients and coinfection with other transfusion-transmissible viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 78 publications
1
18
0
1
Order By: Relevance
“…In addition, unexpectedly high anti-HEV immunoglobulin G (IgG) seroprevalence among the general population has been reported from some industrialized countries, although the rates varied considerably between reports, ranging from 2 . 3 to 33 % [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, unexpectedly high anti-HEV immunoglobulin G (IgG) seroprevalence among the general population has been reported from some industrialized countries, although the rates varied considerably between reports, ranging from 2 . 3 to 33 % [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Toyoda et al reported 16.3% HEV seropositivity among hemophilia patients. They also suggested that the parenteral transmission of HEV may have occurred in Japanese patients with hemophilia via non-virus-inactivated coagulation factors (34). Other studies in different countries showed lower HEV seropositivity among hemophilia patients (45)(46)(47)(48) than Japan.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, some effective examinations such as blood-donor screening, viral inactivation of plasma-derived products, and development of recombinant clotting factors are used to reduce viral exposure (31). Several studies that were done in Japan reported high prevalence of HAV and HEV infection among hemophilia patients compare to healthy individual (control group) (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…In der Literatur sind nur wenige Untersuchungen von Hämophiliepatienten berichtet worden [196,197]; in keiner dieser Untersuchungen gab es Hinweise auf ein erkennbares HEV-Infektionsrisiko durch Gerinnungspräparate. Allerdings wurde in einer japanischen Studie bei äl-teren Hämophiliepatienten, die auch mit nicht virusinaktivierten Gerinnungsprä-paraten behandelt worden waren, eine erhöhte Antikörperprävalenz festgestellt [198]. Des Weiteren wurde kürz-lich aus Kanada und Frankreich berichtet, dass HEV durch SD-Plasma übertra-gen werden kann [199,200].…”
Section: Definition Von Ausschlusskriterienunclassified